Technique of complex slime water treatment of coal-mining branch; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Solodov G. А.; Zhbyr Е. V.; Papin А. V.; Nevedrov А. V. (Chemistry, 2007)
Заглавие с титульного листа